Progress and application of intelligent fluid supply technology in working face - Ran LI; Bo LIU; Dalong WANG; Jingbin CHEN; Tongcheng WANG; Rulin ZHOU; Jianqiang WANG; Kangkang ZHAO; Yuanzheng YU; Huaixin QIN; Mingliang LIU; Chao WANG (Meitan kexue jishu, 2022)
Intelligent fluid supply technology in working face is one of the core technologies of intelligent mining. In order to solve the requirements of high data transmission rate, high transmission stability and high data processing ability in the intelligent work face, a centralized-distributed emulsion station control system based on the 100 megabit industrial Ethernet was developed, fault prediction and health management technology and intelligent on-demand liquid supply control technology were studied, which improves intelligent control function, and the development demand of the working media quality assurance technology of the work face hydraulic system was analyzed, and key technologies such as underground integrated reverse osmosis (RO) water treatment technology, high-efficiency multi-stage filtration technology, fully automated emulsion automatic ratio and concentration correction technology and other key technologies were innovated. In order to overcome the key technical problems such as high-strength corrosion-resistant materials, reliability technology of the suction and discharge valves under pure water medium and pure water resistivity assurance technology, the development of intelligent fluid supply system under pure water condition has promoted the development of green mining technology. The core technical problems such as unattended intelligent safety control technology, timely and rapid liquid supply and return relay technology, integrated multi-parameter safety monitoring of long-distance supply pipeline technology with integrated multi parameter monitoring have been overcome, and the problems of remote safe and efficient liquid supply in mines with complex geological conditions have been solved.. This achievement has been popularized and applied in the fully mechanized mining and fully mechanized caving working faces of thin and medium thick coal seams in Shendong Mining Area of National Energy Group, Shanxi Mining Area of China Coal Energy Group, and Yankuang Mining Area of Shandong Energy Group, meeting the demand for liquid supply technology and equipment in the development of intelligent mining at this stage.